Stress Level Detection using Fuzzy Logic / Nor Husna Nabila Khuzaini - Khuzaini, Nor Husna Nabila (2020)
Stress can affect aspects of your life, including your emotions, behaviour, thinking ability, and physical health. The stress level might not be the same with other people, it is needed to ourselves for take the step of precaution and meet the doctor/therapist. This enhancement is in particular relative in emotional memory. Stress become a serious issues nowadays. There are many physical and emotional symptoms of stress that give effect our healthy. The continuous presence of stress can lead to countless terrible fitness effects, such as excessive blood pressure, lack of sleep, susceptibility to infections, and cardiovascular disease. This study aim to determine, develop and evaluate the system of level detection using Fuzzy logic. But, how do you try to detect and check the stress level in our lifestyle? In this paper, the system were design to calculate the data collected from the expertise. This fuzzy logic system were successful develop. The result indicate in stress level detection based on fuzzy logic system that provide the symptom of stress and the facial emotion. The future researcher need to identify the other algorithm that could strengthen the effectiveness of these system.